Anodal Transcutaneous Spinal Direct Current Stimulation (tsDCS) Selectively Inhibits the Synaptic Efficacy of Nociceptive Transmission at Spinal Cord Level. (21st November 2018) - Lenoir, Cédric; Jankovski, Aleksandar; Mouraux, André
Highlights: Low-thoracic tsDCS selectively affects nociceptive responses from the lower limbs. Low-thoracic tsDCS does not affect non-nociceptive responses from the lower limbs. Cervical tsDCS does not affect any responses from the upper and lower limbs. tsDCS aftereffects are likely due to synaptic modulation and not to anodal blockade. Abstract: Recently studies have aimed at developing transcutaneous spinal direct current stimulation (tsDCS) as a non-invasive technique to modulate spinal function in humans. Independent studies evaluating its after-effects on nociceptive or non-nociceptive somatosensory responses have reported comparable effects suggesting that tsDCS impairs axonal conduction of both the spino-thalamic and the medial lemniscus tracts. The present study aimed to better understand how tsDCS affects, in humans, the spinal transmission of nociceptive and non-nociceptive somatosensory inputs. We compared the after-effects of anodal low-thoracic, anodal cervical and sham tsDCS on the perception and brain responses elicited by laser stimuli selectively activating Aδ-thermonociceptors of the spinothalamic system and vibrotactile stimuli selectively activating low-threshold Aβ-mechanoreceptors of the lemniscal system, delivered to the hands and feet. Low-thoracic tsDCS selectively and significantly affected the LEP-N2 wave elicited by nociceptive stimulation of the lower limbs, without affecting the LEP-N2 wave elicited by nociceptive stimulation of the upper limbs, and without affecting the SEP-N2 wave elicited by vibrotactile stimulation of either limb. This selective and segmental effect indicates that the neuromodulatory after-effects of tsDCS cannot be explained by anodal blockade of axonal conduction and, instead, are most probably due to a segmental effect on the synaptic efficacy of the local processing and/or transmission of nociceptive inputs in the dorsal horn.